Nano-crystalline lead sulfide thin films using the chemical bath deposition: synthesis and characterization / M. Husham, Z. Hassan and Ahmed A. Al-Dulaimi - M, Husham; Z, Hassan; Al-Dulaimi, Ahmed A (2017)
Nanocrystalline lead sulfide (PbS) thin films have been successfully grown on glass substrate using the chemical bath deposition technique. Microwave oven was used as a heating source to facilitate the growth process of the thin films. Aqueous solutions of lead nitrate Pb(NO3) and thiourea [SC(NH2)2] were used as lead and sulfur ion sources, respectively. Structural, morphological and optical analyses revealed good quality growth of nanocrystalline PbS thin films. This study introduced a facile and low cost method to prepare high quality nanocrystalline PbS thin films in a relatively short growth time for optoelectronic applications.